Biomedical outcomes and cardiovascular risks in Chinese adults with type 2 diabetes in the metabolic management center program: A longitudinal comparative study - Zhanpeng He; Hui Cheng; Zhihui Jia; Zimin Niu; Yu Ting Li; Wenyong Huang; Vivian Yawei Guo; Zhiran Su; Yao Jie Xie; Jie Shen; Harry HX Wang (Journal of Diabetes Investigation)
ABSTRACT Aims To assess the extent to which biomedical outcomes and cardiovascular risk profile were improved in the management of Chinese patients with type 2 diabetes enrolled in the metabolic management center (MMC) program. Materials and Methods We performed propensity score matching of diabetic patients in the MMC program for at least 12 months to those with diabetes under usual primary care, based on age, sex, fasting plasma glucose (FPG) level, and diabetes duration. Difference‐in‐difference analysis was conducted to compare changes in biomedical outcomes, attainment of treatment targets, and cardiovascular disease (CVD) risk reduction. Results Of 557 pairs of diabetic patients matched 1:1 (n = 1,114), the MMC cohort exhibited greater improvements in FPG (−0.84 mmol/L, 95% confidence interval [CI] −1.22 to −0.46, P < 0.001), diastolic blood pressure [BP] (−2.08 mmHg, 95%CI −3.21 to −0.94, P < 0.001), body mass index [BMI] (−0.29 kg/m2, 95%CI −0.51 to −0.07, P = 0.009), low‐density lipoprotein cholesterol (0.13 mmol/L, 95%CI 0.04–0.23, P = 0.008), high‐density lipoprotein cholesterol (0.05 mmol/L, 95%CI 0.01–0.08, P = 0.017), and 10‐year CVD risk (Framingham CVD risk, −0.94%, 95%CI −1.71 to −0.17, P = 0.017; atherosclerotic CVD risk, −0.77%, 95%CI −1.34 to −0.20, P = 0.009) when compared to the usual primary care cohort after adjustment for confounders. More patients in the MMC cohort achieved treatment targets with lifestyle modifications than their counterparts under primary care. Conclusions Enrolment in the MMC program appears promising in the management of FPG, BP, BMI, lifestyle, and CVD risk in diabetic patients, suggesting the necessity of incorporating the MMC program into routine primary care.